Faktor – Faktor Yang Berhubungan Dengan Perilaku Pelayanan Kader Posyandu Di Kelurahan Sumur Batu Jakarta Pusat Tahun 2023 - Innes Resnasari Agustianty; Rini Handayani; Namira Wadjir Sangadji; Ade Heryana (Jurnal Anestesi, 2023)
The average coverage of under-five weighing in Indonesia in 2021 is 69.0% of children per month. This number has increased from 2020 of 61.3% of children per month. Health cadres at Posyandu play an important role in efforts to increase public awareness of health as guidance and supervision of promotive and preventive efforts. The achievement of Posyandu goals is inseparable from the behavior of Posyandu cadres. The formation of cadres is an educative approach method, to activate the community in development, especially in the health sector. Posyandu cadres are a very important component for the implementation of Posyandu properly. Objective: To find out the factors related to the service behavior of Posyandu cadres in Sumur Batu Village, Central Jakarta. Research Methods: This type of research is a quantitative study with a cross-sectional research design. The population and sample in this study were all Posyandu cadres in Sumur Batu Village, totaling 72 people. The sample technique used is total sampling. Research results: There is no relationship between attitude (p-value = 0.102) and service behavior of Posyandu cadres, there is a relationship between the support of community leaders (p-value = 0.004) and service behavior of Posyandu cadres, and there is no relationship between family support (p-value = 0.979) with the service behavior of Posyandu cadres in Sumur Batu Village, Central Jakarta in 2023.